2012
DOI: 10.1371/journal.pone.0050616
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induces Nuclear-to-Cytosol Shift of hMSH3, a Potential Mechanism for EMAST in Colorectal Cancer Cells

Abstract: BackgroundElevated microsatellite alterations at selected tetranucleotide repeats (EMAST) is a genetic signature observed in 60% of sporadic colorectal cancers (CRCs). Unlike microsatellite unstable CRCs where hypermethylation of the DNA mismatch repair (MMR) gene hMLH1’s promoter is causal, the precise cause of EMAST is not clearly defined but points towards hMSH3 deficiency.AimTo examine if hMSH3 deficiency causes EMAST, and to explore mechanisms for its deficiency.MethodsWe measured −4 bp framshifts at D8S3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 21 publications
5
75
0
Order By: Relevance
“…As mentioned above, cumulative evidence supports the idea that the etiology of MSI-L/EMAST formation in cancer genome is the inflammation-induced loss of nuclear MSH3 in dividing cells (10,37,39). Therefore, it is reasonable to speculate that a sub-group of MSI-L/EMAST CRC may be associated with pathogenic infections of microbiota including Fusobacterium .…”
Section: Fusobacterium Infection Is Associated With Msi-l/emastsupporting
confidence: 56%
See 2 more Smart Citations
“…As mentioned above, cumulative evidence supports the idea that the etiology of MSI-L/EMAST formation in cancer genome is the inflammation-induced loss of nuclear MSH3 in dividing cells (10,37,39). Therefore, it is reasonable to speculate that a sub-group of MSI-L/EMAST CRC may be associated with pathogenic infections of microbiota including Fusobacterium .…”
Section: Fusobacterium Infection Is Associated With Msi-l/emastsupporting
confidence: 56%
“…The frequent incidence of EMAST in CRCs was confirmed by two other studies (34,35). The fact that EMAST is due to the loss of MSH3 was also proven by other studies using tissue cultured human cells (36,37). Later, Adam et al found patients with bi-allelic inactivation mutations at the MSH3 locus who suffered from colorectal adenoma polyposis syndrome.…”
Section: Characteristics Of Fusobacterium-associated Crcssupporting
confidence: 53%
See 1 more Smart Citation
“…While it is important to identify Lynch syndrome from sporadic cases of colorectal cancer as patients with Lynch syndrome have recurring bouts of cancer development, the separation between Lynch-like and Lynch syndrome, to date, is not as clear cut. As shown in the table , there are a number of recognized mechanisms to inactivate DNA MMR function (4-8,10,12-18), several of which do not directly affect the sequence of the DNA MMR genes. These and other mechanisms could be operative in the germline of Lynch-like patients.…”
mentioning
confidence: 99%
“…As recently described, a group of frequent colic tumors with elevated microsatellite alterations at selected tetranucleotide repeats (EMAST), usually related to MSH3 gene loss, presents a bad prognosis. EMAST can be associated with any kind of colon cancer, both hypermutated and nonhypermutated, and usually a high metastatic rate [86][87][88].…”
Section: Genomic Instability As a Cause Of Heterogeneitymentioning
confidence: 99%